Comparative study of one-dimensional NiCo alloy nanostructures assembled by in situ and ex situ applied magnetic fields - 吴明在 全桂英 刘艳美 马永青 戴鹏 张立德 (Transactions of Nonferrous Metals Society of China, 2009)
For the study of magnetic field-assisted assembly behavior, one-dimensional （1D） NiCo alloy nanostructures were solvothermally obtained at 180 ℃ under an in situ magnetic field （the magnetic field as applied during the chemical reduction） and ex situ field （after the chemical reduction was finished）. Microscopic morphology and magnetic properties differences were investigated using scanning electronic microscope （SEM） and vibrating sample magnetometer （VSM） for these products. Magnetic measurement results show that 1D ordered microstructures under in situ magnetic field possess higher saturation magnetization Ms, remnant magnetization Mr, coercivity Hc and reduced magnetization Mr/Ms than 1D ordered microstructures under ex situ field, and the four magnetic parameters of the two ordered microstructures are much higher than those randomly distributed alloy particles prepared in the absence of external magnetic field.